2010
DOI: 10.1587/transinf.e93.d.3223
|View full text |Cite
|
Sign up to set email alerts
|

Parallelization of Computing-Intensive Tasks of the H.264 High Profile Decoding Algorithm on a Reconfigurable Multimedia System

Abstract: SUMMARYThis paper proposes approaches to perform HW/SW (Hardware/Software) partition and parallelization of computing-intensive tasks of the H.264 HiP (High Profile) decoding algorithm on an embedded coarse-grained reconfigurable multimedia system, called REMUS (REconfigurable MUltimedia System). Several techniques, such as MB (MacroBlock) based parallelization, unfixed sub-block operation etc., are utilized to speed up the decoding process, satisfying the requirements of real-time and high quality H.264 appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Other studies, such as parallelization of computeintensive tasks in H.264 based on reconfigurable multimedia system [11], have also shown that the block-based wordlevel calculations comprise a majority of the decoding workloads in all the video decoding standards. For instance, an experiment of H.264 decoding is performed on a RISC processor to measure the workloads of MC, DF, and inverse quantization and transformation (IQT).…”
Section: Algorithm Analysismentioning
confidence: 99%
“…Other studies, such as parallelization of computeintensive tasks in H.264 based on reconfigurable multimedia system [11], have also shown that the block-based wordlevel calculations comprise a majority of the decoding workloads in all the video decoding standards. For instance, an experiment of H.264 decoding is performed on a RISC processor to measure the workloads of MC, DF, and inverse quantization and transformation (IQT).…”
Section: Algorithm Analysismentioning
confidence: 99%
“…It has been shown in [11] that the block-based word-level calculations comprise a majority of the decoding workloads. For instance, an H.264 decoding application is performed on a RISC processor and the measured MC, deblocking, and Inverse Quantization and Transformation (IQT) workloads account for more than 75% of the total workload as illustrated in Fig.…”
Section: Algorithm Analysis and Design Considerationmentioning
confidence: 99%
“…2. Measured computational workload of a typical H.264 decoding application (video steam "foreman" on an ARM926EJ processor) [11]. (CGRAs), the computation tasks are usually divided into many small kernels (compiled in the forms of multiple contexts) which are then mapped on and executed by the array repeated [14].…”
Section: Algorithm Analysis and Design Considerationmentioning
confidence: 99%
“…A heterogeneous platform integrated in a SoC comprising both specialized hardware accelerators and general-purpose processors is therefore a widely accepted solution [7], [8], [19].…”
Section: A Computing Environmentmentioning
confidence: 99%